Law, political stability, tourism management and economic development in sub-Saharan Africa - Simplice Asongu; Mushfiqur Rahman; Joseph Nnanna (African Governance and Development Institute (AGDI), 2022)
This study complements the extant literature by assessing how the rule of law and political stability modulate tourism development dynamics (i.e. tourism receipts and tourism expenditure) to affect economic development in terms of gross domestic product (GDP) per capita. The study focuses on 47 countries in sub-Saharan Africa (SSA) with data for the period 2002 to 2018 and the empirical evidence is based on the Generalized Method of Moments. The study finds that: (i) the rule of law modulates both tourism receipts and tourism expenditure for overall positive effects on economic development and (ii) political stability modulates tourism receipts for an overall positive impact on economic development. Policy implications are discussed.
Keywords: O10; O40; Z3; Z32; 330; Tourism Management; Economic Growth; Sub-Saharan Africa